Небывалая игра: повести / пер. с нем. П. Л. Френкель ; худож. В. С. Пощастьев - Нестлингер Кристине (ЮНАЦТВА, 1990)
Экземпляры: Д.О. (20201123) / Инвентарный номер: 48100 / Цена: 2.60 / Сис.шифр: 84(3) / Авт.знак: Н 56 / ГРНТИ: 17.82 / ББК: 84(4Авс)